Characterization of palm oil fuel ash and eggshell powder as partial cement replacement in concrete - N. H. A., Khalid; N. N. A., Rasid; A. R., Mohd.Sam; N. H. A. S., Lim; M., Ismail; L., Zardasti; A., Mohamed; Z. A., Majid; Nur Farhayu, Ariffin (IOP Publishing, 2018)
The utilization of palm oil fuel ash (POFA) and eggshell powder (ESP) in concrete as a cement replacement is possible as green concrete materials. However, the POFA has original cellulose and physical modification is needed. This paper presents the characterization of POFA; unground POFA (UPOFA) and ground POFA(GPOFA) and ESP under microstructure examination includes x-ray fluorescence (XRF), scanning electron microscopy (SEM), and particle size analyzer (PSA). Then, the POFA-ESP as a cement replacement in concrete was investigated. Optimum mix proportion of POFA-ESP concrete was determined from compression test and GPOFA-ESP and UPOFA-ESP were through further investigation on pozzolanic reaction under x-ray diffraction (XRD) test at 14 days-concrete age. It was found that the combination of GPOFA-ESP as a cement replacement produced a concrete enhanced the compressive strength than normal concrete. ESP in this study seems like a catalyst which acting as mild accelerator or booster to improve the early age of strength development without disturb the later strength development of concrete. In addition, combination of GPOFA-ESP could increase the C-S-H gel at early age of concrete. It can be concluded that the combination of GPOFA-ESP had dual function; ESP and GPOFA took at early and later strength development, respectively.